Evaluation of in-person continuing education programs from the perspective of ward nurses - Nasrin Galehdar; Maryam Ehsani; Alireza Irajpour; Soheila Jafari-Mianaei (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Assessing how programs are implemented from the perspective of the learners themselves is one of the most effective ways to improve the quality of continuing education. The aim was to evaluate the implementation of in-person continuing education programs from the perspective of nurses. METHODOLOGY: Setting of the study was the selected hospital of Isfahan University of Medical Sciences (Al-zahra hospital). This study is a descriptive cross-sectional one. Using a researcher-made questionnaire, the implementation of continuing education programs in four areas of the aim, educational techniques, educational content, and educational field was evaluated. The sample consisted of 236 nurses working in these hospitals who participated in the study through convenience sampling. Data were analyzed by SPSS software version 19 using descriptive statistics. RESULTS: Based on the results, "the need for new content learning" was mentioned as the first priority in continuing education programs. The majority of participants scored each of the following domains (aim, educational techniques, educational content, and education field) as well as all items related to the continuing education program evaluation as "moderate." CONCLUSION: Most nurses assessed the implementation of in-person continuing education programs implemented in Isfahan University of Medical Sciences in general and in each of the domains as "moderate." Therefore, in order to improve the quality of programs, it is necessary to take steps to match the goals with the needs of learners, improve teaching techniques, improve the quality of program contents, and optimize the scope of the programs.